Social Media Use and its Connection to Anxiety and Gender - Baldur Abraham Ólafarson 1985- (2018)
In recent years the use of social media has grown substantially among young people. At the same time research has shown that occurrence of anxiety has also increased, especially among young girls. The aim of this study was to look at whether increased use of social media has an effect on increased reported anxiety among young people and if there was any difference between genders. The data used in this study came from a study that was commissioned by The Icelandic Centre for Social Research and Analysis (ICSRA) which gave a questionnaire to students in 8th to 10th grades in Iceland. The results show that girls spend more time on social media than boys and their anxiety levels are also higher. That can be an indication that time spent on social media has a direct increasing effect on anxiety, more with girls than boys. Undanfarin ár hefur notkun samfélagsmiðla aukist mikið meðal ungs fólks. Á sama tíma hafa rannsóknir sýnt að kvíði fer vaxandi, einkum hjá ungum stúlkum. Markmið þessarar rannsóknar er að kanna hvort aukin notkun samfélagsmiðla hefur áhrif á aukningu kvíðatilfella hjá ungu fólki og hvor munur væri á kynjum. Framkvæmd rannsóknarinnar var á þá leið að notuð voru gögn frá Rannsóknum og greiningu sem lagði spurningarlista fyrir nemendur í 8. -10. bekk grunnskóla á Íslandi. Niðurstöðurnar sýndu að stúlkur verja að staðaldri meiri tíma á samfélagsmiðlum og eru kvíðnari. Það bendir til þess að tíminn sem unga fólkið ver á samfélagsmiðlum hafi bein áhrif á kvíða, meira hjá stúlkum en drengjum.